النظام الضريبي الجزائري بين هدفي العدالة والتحصيل - بوكرش ﷴ امين (جامعة البليدة2؛كلية العلوم الاقتصادية العلوم التجارية وعلوم التسيير, 2025)
تاول هه اﻷوحة در قة مع إلى 2010 للام الي الائ خﻼل الفة الة م ي 2021 ، في ل الات اﻻقادة واﻻجاة الت بها م ة الولة الائولة ، وض سعي ال لق الازن ب العالة ة اﻻجاة والفعالة الال .ام اسة م اﻹار الفاي العام لل تل الر الي الائة أو ، معضة أهافه اﻷساسة، ساء ان اقادة، مال ى ح ة، إضافة اجا إلى مناته م تع جائي، إدارة ضة، ل ضي، ومع ملف الة. كا تعى ا ائ ﻷوحة أهة خاصة لار اﻹصﻼحات الائة الي اشتها ال و اسة تقم الر ة ة الاش ً ا ﻷه الائ العة في الام الائي الائ، ساء ً دق على اح ً تلﻼ أر ة الات، الة على الخل اﻹجالي، والس على الا الهي، أو غ الاش على مل الس ها على الة الافة والس الاخلي على اﻻسهﻼك، مع تضح ة حابها، مال تقها، وأث اللف. وتقل اﻷوحة إلى تلل العالة الائة م مر ن وعلي، ل الى ل قة اسة تللة مع در ادات الة السة في الائ لر اﻹية انات 2021–2010 خﻼل الف ا على ب ً ، اعاد وحائات دقة، خارج قاع الوقات .ا ك ت ات تلل الغ الائي وانعاساته على الف اﻻجاة اللفة، ما ح بق م فعالة الام الي في تق العالة اﻻجاة. اسة إلى أن الام الا خل الر ال عاني م ئي الائ ﻻ ياكل م الة في لة تعل عم الع تزع العء الي، ضعف اﻹدارة، وعم فعالة الل، وهي ر أم تع ة تق أهاف ال XX اﻻقادة واﻻجاة .ورة وتصي اﻷوحة اء إج إصﻼحات ة جائة شاملة ، جر ت ت على العالة، ا ، ال لة قة، وتسع القاعة الائ. اللات الفاحة :ي ا ، الام ال العة ي ، لة الائ ائي ، الل ال ، الغ ال ، الفعالة الائة This dissertation presents a comprehensive study of the Algerian tax system during the period from 2010 to 2021, within the context of the economic and social challenges faced by the country and the State's efforts to strike a balance between social justice and fiscal efficiency. The study begins with a general conceptual framework of the tax system, outlining its main objectives—economic, financial, and social—alongside its core components: tax legislation, tax administration, tax structure, and the community of taxpayers. Particular attention is given to the trajectory of tax reforms undertaken by Algeria. The dissertation also provides a detailed analysis of the major taxes in the Algerian fiscal system, both direct taxes—such as the Corporate Income Tax (IBS), the Global Income Tax (IRG), and the Professional Activity Tax (TAP)—and indirect taxes, including the Value Added Tax (VAT) and the Domestic Consumption Tax (TIC). The study highlights their scope, calculation methods, and impact on taxpayers. The study then delves into the concept of tax justice, examining it from both theoretical and practical perspectives. It concludes with an in-depth analytical evaluation of the evolution of Algeria’s official tax revenues between 2010 and 2021, relying on accurate data and statistics, especially outside the hydrocarbons sector. Furthermore, it analyzes the tax burden structure and its implications for different social groups, offering a critical assessment of the effectiveness of the tax system in achieving social justice. The findings reveal that the Algerian tax system still suffers from structural issues related to the unequal distribution of tax burdens, administrative inefficiencies, and ineffective tax collection, which hinder the achievement XXII of economic and social development goals. The dissertation recommends implementing comprehensive and fundamental tax reforms based on the principles of equity, simplification, digitization, and broadening the tax base
دراسة حالة الجزائر
Keywords: النظام الضريبي; العدالة الجبائية; الضغط الجبائي